Elevated CA 125 in a CASE of Leaking Endometrioma - Svetha Rao; Supuni Kapurubandara; Anbu Anpalagan (Case Reports in Obstetrics and Gynecology)
Extremely elevated CA 125, usually suggestive of ovarian malignancy, can be found in physiological or benign conditions such as endometriosis. We present a case of an extremely elevated serum CA 125 level in a patient with stage four endometriosis and bilateral unruptured ovarian endometriomas, with evidence of leakage unilaterally. To avoid costly and unnecessarily invasive tests and procedures it is important to consider the differential diagnosis of endometriosis and/or leaking endometrioma in patients with a profoundly elevated CA 125 level.